Pelatihan Pembuatan Piscok Berbahan Dasar Pisang Kepok Sebagai Upaya Pemberdayaan Ekonomi Masyarakat: Pengabdian - Ulan Paramita; Elza Rahman Dania; Priska Septiana; Ranti Septiana Ningsi; Sefni Yudiantri; Uswatun Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Micro, Small and Medium Enterprises (MSMEs) are currently a new way for people to become entrepreneurs. However, the observations made produced information on partner needs in several aspects, such as management aspects, production aspects, and human resources and technology aspects. Some MSMEs feel less able to attract customers to be interested in the products they sell. Like MSME piscok (chocolate banana) actors who have the same problem about how to attract consumers. The target output of increasing the quantity and quality of production, skills, and business processes that run more effectively and efficiently in general has been achieved through this community service process. This community service program through training aims to educate how to introduce products so that they can attract consumers easily. There are several important factors to make our production get attention from potential consumers such as having a logo and product name, giving a tagline to interest consumers, and offering products using social media. The results of the implementation of the training were to provide a positive response, namely by explaining what the logo, banner, menu list, packaging (stamp), and promotion on social media wanted by the participants of the MSME Piscok branding training.